Journal of Language and Linguistic Studies (2016)
Journal of Language and Linguistics Studies (JLLS) is a professional, double blind peer-reviewed international journal that aims to involve scholars not only from Turkey, but also from all international academic and professional community. The journal
provides a platform for different theoretical and thematic approaches to linguistics and language teaching.